2010
DOI: 10.1073/pnas.1004104107
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic tuning of the chemoprotective natural product sulforaphane

Abstract: Sulforaphane [1-isothiocyanato-4-(methylsulfinyl)butane], a naturally occurring isothiocyanate derived from cruciferous vegetables, is a highly potent inducer of phase 2 cytoprotective enzymes and can protect against electrophiles including carcinogens, oxidative stress, and inflammation. The mechanism of action of sulforaphane is believed to involve modifications of critical cysteine residues of Keap1, which lead to stabilization of Nrf2 to activate the antioxidant response element of phase 2 enzymes. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
125
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(135 citation statements)
references
References 46 publications
7
125
0
Order By: Relevance
“…These researches were dedicated primarily to the simplification of SFN structure by using a rigid core between the sulfinyl sulfur and the isothiocyanate group for instance, or by eliminating or replacing the chiral sulfinyl group. Recently, researches were directed toward the modulation of the isothiocyanate reactivity, by using a less electrophilic functionality [33].…”
Section: (R S )-1-isothiocyanato-4-(methylsulfinyl)-butane (Sulforaphmentioning
confidence: 99%
“…These researches were dedicated primarily to the simplification of SFN structure by using a rigid core between the sulfinyl sulfur and the isothiocyanate group for instance, or by eliminating or replacing the chiral sulfinyl group. Recently, researches were directed toward the modulation of the isothiocyanate reactivity, by using a less electrophilic functionality [33].…”
Section: (R S )-1-isothiocyanato-4-(methylsulfinyl)-butane (Sulforaphmentioning
confidence: 99%
“…Very recently, a series of sulfoxythiocarbamate analogs of sulforaphane were synthesized that retain the structural features important for high inducer potency, i.e. a sulfinyl or a carbonyl group at a specific distance from the electrophilic functional group (13).…”
mentioning
confidence: 99%
“…54 We also found that such sulfoxythiocarbamate derivatives, by virtue of their sulfhydryl reactivity, destabilize HSP90 client proteins and induce the HSR 55. With this knowledge, we studied the ability of PEITC to inhibit HSP90 56.…”
Section: Peitc Activates the Hsf1‐dependent Heat Shock Responsementioning
confidence: 97%